2015
DOI: 10.1159/000430224
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCL21 Antibody Attenuates Infarct Size and Improves Cardiac Remodeling After Myocardial Infarction

Abstract: Background/Aims: Over-activation of cellular inflammatory effectors adversely affects myocardial function after acute myocardial infarction (AMI). The CC-chemokine CCL21 is, via its receptor CCR7, one of the key regulators of inflammation and immune cell recruitment, participates in various inflammatory disorders, including cardiovascular ones. This study explored the therapeutic effect of an anti-CCL21 antibody in cardiac remodeling after myocardial infarction. Methods and Results: An animal model of AMI gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Therefore, inhibitors of MMP-9 production from macrophages may be useful to prevent plaque rupture. Furthermore, MMP-9 deletion was proved to improve left ventricular function in remodeling myocardium post-MI [43]. In this study, we found that green tea polyphenol EGCG significantly inhibited the expression and activity of MMP-9 in a concentration-dependent manner in PMA-induced macrophages.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, inhibitors of MMP-9 production from macrophages may be useful to prevent plaque rupture. Furthermore, MMP-9 deletion was proved to improve left ventricular function in remodeling myocardium post-MI [43]. In this study, we found that green tea polyphenol EGCG significantly inhibited the expression and activity of MMP-9 in a concentration-dependent manner in PMA-induced macrophages.…”
Section: Discussionmentioning
confidence: 55%
“…6 Studies in animals reported that the inhibition of the reparative process can reduce the infarct size and improve the evolution of the VR. 44,45 However, the early use of anti-inflammatory drugs after infarction promoted the thinning and expansion of the infarct zone in animals and increased the incidence of cardiac rupture in patients. 46 Thus, a defect in the healing process or an increase in the infarct size and parietal stress were the main determinants of the expansion and the appearance of adverse clinical events, heart failure, and death.…”
Section: Galectin-3 On Healing and Remodelingmentioning
confidence: 99%
“…Macrophages in an injured spinal cord have dynamic phenotypes and functions that can change based on the spinal lesion microenvironment (Stout and Suttles, 2004; Menzies et al, 2010). CCL21 and its receptor CCR7 are widely expressed in T cells, dendritic cells, fibroblasts, smooth muscle, and intravascular cells, and CCL21 contributes to inflammation and remodeling of the extracellular matrix (Jiang et al, 2015). CCR7 has an important role to migrate dendritic cells and/or T cells from brain parenchyma to deep cervical lymph nodes for immune response; CCR7 deficient inflammatory cells are retained in the central nervous system (CNS) and exacerbate CNS autoimmune diseases, including multiple sclerosis (KivisĂ€kk et al, 2004; Clarkson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%